Neuropsychological investigation of amateur boxers. Issue 3 (September 1994) - Butler, R J
Abstract : Amateur boxing is faced with criticism over the potential damage the sport inflicts on those who participate. The most sensitive measure of early neurological dysfunction is neuropsychological investigation. Ten studies employing such assessments on 289 amateur boxers are reviewed. The forms of analysis undertaken include controlled comparison with other sportsmen, of both active and former boxers, detailed pre- and post-bout analysis, analysis of the influence of within-boxing variables, length of career, level of competition and prospective longitudinal investigation. Amateur boxers were found to exhibit no signs of neuropsychological dysfunction in any analysis. However some trends emerged suggesting a long career in amateur boxing might reduce fine motor reactions, although such findings are within the normal range and do not represent central neuropsychological functioning. Thus amateur boxing does not appear to expose individuals to neurological dysfunction.